Role Of Factors of System of Oxide of Nitrogen in Dynamics of Formation at Experimental Animals of The Metabolic Syndrome - Kasimova G. Z. (Zien Journals, 2022)
Research objective - to investigate a nature of activity of ferments eNOS and iNOS, expressions NO andONO2-in serum of blood of rabbits in dynamics of formation of a metabolic syndrome.
Keywords: metabolic; nitroergic; dysfunction; endothelium